Purging of highly deleterious mutations through severe bottlenecks in Alpine ibex - Christine Grossen; Frédéric Guillaume; Lukas F. Keller; Daniel Croll (2019)
Abstract Human activity caused dramatic population declines in many wild species. The resulting bottlenecks have a profound impact on the genetic makeup of a species with unknown consequences for health. A key genetic factor for species survival is the evolution of deleterious mutation load, but how bottleneck strength and mutation load interact lacks empirical evidence. Here, we take advantage of the exceptionally well-characterized population bottlenecks of the once nearly extinct Alpine ibex. The species survived one of the most dramatic bottlenecks known for successfully restored species. We analyze 60 complete genomes of six ibex species and the domestic goat. We show that historic bottlenecks rather than the current conservation status predict levels of genome-wide variation. By retracing the recolonization of the Alps by Alpine ibex, we find genomic evidence of concurrent purging of highly deleterious mutations but accumulation of mildly deleterious mutations. This demonstrates how human-induced severe bottlenecks caused both relaxed selection and purging, thus reshaping the landscape of deleterious mutation load. Our findings also highlight that even populations of ~1000 individuals can accumulate mildly deleterious mutations. Hence, conservation efforts should focus on preventing population declines below such levels to ensure long-term survival of species.